AN ANALYSIS ADDRESS TERMS OF TOLAKI LANGUAGE - Haslan Haslan (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
Abstract The research focused on address term of Tolaki language which is conducted among the people who include in family. Which, the main objectives of the research namely (1) to find out the data about the address terms of Tolaki language (2) to describe the use of every address terms of Tolakinese society in their daily social interaction. This research uses qualitative descriptive analysis by applying some techniques of collecting data namely ( 1) Observation and participation (2) Noting. After the data being collected, the writer analyzes them through the following steps: (1) Transcribing the data, (2) Making classification of gathered data relating to address terms, (3) Making description for last generalization objectively based on the script of data will be gotten in the field of the research. The result of this research shows that there are thirty kinds of address terms of Tolaki language gathered in this research namely pue, mbue, ina, ama, naina, ma’ama, awo, awo langgai, awo ndina, ma’ama awo, naina awo, ama awo, ina awo, ka’aka awo, hai awo, pue awo, wali baisa, Ela, hine, bea, asa, sege, bio, wuto, tina, tie, mburi, ana, ka’aka and hai. Key Words: Tolaki, Address Term, Language